Means to support the object traces in the conceptual modeling systems - Yu. Ismailova, L.; V. Kosikov, S.; E. Wolfengagen, V.; V. Mazurova, J. (International Journal of Engineering and Technology, 2018)
The paper considers the problem of conceptual modeling of the domains, in which a large number of changes takes place, possesses a number of specific features. Some of the features are connected to the nature of the ongoing changes. The problem becomes severe when the domain contains a large quantity of independently acting agents that can produce changes in various parts of the model, the sets of interrelated data being changed by different agents independently.Besides that, when supporting the dynamic nature models the possibilities of future changes in model objects might largely be deter- mined not only by their current state, but also by the past state - history of the objects in the model. The support to such history inside the current state of the object can be difficult, cumbersome or impractical for other reasons, which also stimulates the search for new ap- proaches to ensure the map of the changes of objects in the domain model.It is offered to receive the decision by single out the individual information identities, that can be called state trajectories from the con- ceptual point of view and object traces from the implementation point of view. They represent a sequence of changes in the state of mod- el objects essential for its support. The traces can fix not all changes of the corresponding objects, but only those which have an influence on the further behavior of the model. Various ways of supporting of traces are considered. The paper presents an approach to the deter- mination and the support to the traces, based on using a combination of methods of the intensional logic and applicative computational systems.Â